Understanding gendered trait preferences: Implications for client-responsive breeding programs - McDougall, Cynthia; Kariuki, Juliet; Lenjiso, Birhanu Mergesa; Marimo, Pricilla; Mehar, Mamta; Murphy, Seamus; Teeken, Béla; Akester, Michael J.; Benzie, John A.H.; Galiè, Alessandra; Kulakow, Peter A.; Mekkawy, Wagdy; et al. (2022)
Client-responsiveness is a foundation for effectiveness of public sector breeding programs in agriculture, aquaculture and livestock. However, there remains a considerable lack of clarity about what this means, specifically in terms of how programs can be gender-responsive. This study contributes to addressing that need. It does so through sharing higher-level insights emerging from the combined experiences of eight gendered trait preference cases from across nine countries in Asia and Africa. The cases spanned crops, fish and livestock. This study inquires into the nature of gendered trait preference information that can be generated, if there are systematic gendered preference differences and how to understand these, and implications for breeding programs seeking to be more gender-responsive. Key findings include that while not all data are immediately usable by programs, the information that is generated through mixed method, intersectional gender preference assessments usefully deepens and widens programs’ knowledge. The study evidences differences in trait preferences between women and men. It also reveals that these differences are more complex than previously thought. In doing so, it challenges binary or homogenous models of preferences, suggesting instead that preferences are likely to be overlapping and nuanced. The study applies a novel ‘Three models of gendered trait preferences’ framework and sub-framework and finds these useful in that they challenge misconceptions and enable a needed analytical nuance to inform gender-responsive breeding programs. Finally, the study highlights implications and offers a call to action for gender-responsive breeding, proposing ways forward for public breeding programs, teams and funding agencies. These include investments in interdisciplinary capabilities and considerations for navigating trade-offs while orienting to sustainable development goals.